Social Media Use and Depression: The Mediating Role of Public Self-Awareness - Tabo, Chantal Ellis (Archīum Ateneo, 2020)
Studies have linked the relationship between social media use and depression. However, previous researchers noted the presence of a mediating variable that helps strengthen the connection between the two variables. Anchoring on Objective Self- Awareness Theory (Duval & Wicklund, 1972; Wicklund, 1975), this study examines public self-awareness, one’s consciousness of how others might perceive them, as the mediating variable. The study used a cross-sectional survey design, where 221 young adults answered an online survey. Data was analyzed using structural equation modeling. Results show that public self-awareness mediated social media use for coping with negative emotions, but not when social media is used for social interaction. The study also showed a positive correlation between social media used for coping and for social interactions. Data clarified that public self-awareness mediates the relationship between social media use for coping and depression. Social media use mainly for social interactions does not lead to depression through public self-awareness. The Objective Self-Awareness Theory may explain that comparison between the perceived self and perception of one’s online social network may increase one’s level of depression. Using social media to increase one’s social capital may help lessen depression.